Base and The Goals of Islamic Religious Education In Indonesia - Nur Afiyah (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2023)
Islamic education is all forms of coaching efforts carried out in life to demand that humans have personalities in all activities in life in accordance with the values of Islamic teachings. Education implemented by a country is of course based on that country's philosophy or way of life. The educational goals that a country wants to achieve must also be in line with the goals of that country. Likewise with Islamic education, of course Islamic education has a basis and goals that are in line with Islamic teachings . The basis of national education is Pancasila , the 1945 Constitution and the National Education System Law no. 2 in 1989. Meanwhile, the basis of Islamic education is the Koran, Hadith and Ijtihad. The aim of Islamic education is to form Muslim individuals who are in accordance with the values of Islamic teachings.